Suppression of uPAR Retards Radiation-Induced Invasion and Migration Mediated by Integrin β1/FAK Signaling in Medulloblastoma - Nalla, Arun Kumar; Asuthkar, Swapna; Bhoopathi, Praveen; Gujrati, Meena; Dinh, Dzung H.; Rao, Jasti S. (PLOS ONE, 2010)
Background Despite effective radiotherapy for the initial stages of cancer, several studies have reported the recurrence of various cancers, including medulloblastoma. Here, we attempt to capitalize on the radiation-induced aggressive behavior of medulloblastoma cells by comparing the extracellular protease activity and the expression pattern of molecules, known to be involved in cell adhesion, migration and invasion, between non-irradiated and irradiated cells. Methodology/Principal Findings We identified an increase in invasion and migration of irradiated compared to non-irradiated medulloblastoma cells. RT-PCR analysis confirmed increased expression of uPA, uPAR, focal adhesion kinase (FAK), N-Cadherin and integrin subunits (e.g., α3, α5 and β1) in irradiated cells. Furthermore, we noticed a ∼2-fold increase in tyrosine phosphorylation of FAK in irradiated cells. Immunoprecipitation studies confirmed increased interaction of integrin β1 and FAK in irradiated cells. In addition, our results show that overexpression of uPAR in cancer cells can mimic radiation-induced activation of FAK signaling. Moreover, by inhibiting FAK phosphorylation, we were able to reduce the radiation-induced invasiveness of the cancer cells. In this vein, we studied the effect of siRNA-mediated knockdown of uPAR on cell migration and adhesion in irradiated and non-irradiated medulloblastoma cells. Downregulation of uPAR reduced the radiation-induced adhesion, migration and invasion of the irradiated cells, primarily by inhibiting phosphorylation of FAK, Paxillin and Rac-1/Cdc42. As observed from the immunoprecipitation studies, uPAR knockdown reduced interaction among the focal adhesion molecules, such as FAK, Paxillin and p130Cas, which are known to play key roles in cancer metastasis. Pretreatment with uPAR shRNA expressing construct reduced uPAR and phospho FAK expression levels in pre-established medulloblastoma in nude mice. Conclusion/Significance Taken together, our results show that radiation enhances uPAR-mediated FAK signaling and by targeting uPAR we can inhibit radiation-activated cell adhesion and migration both in vitro and in vivo.